Effect of mortality from COVID‐19 on inpatient outcomes. Issue 1 (18th September 2021) - Phillips, Matthew C.; Sarff, Laura; Banerjee, Josh; Coffey, Chase; Holtom, Paul; Meurer, Steve; Wald‐Dickler, Noah; Spellberg, Brad
Abstract: When hospitals first encountered coronavirus disease 2019 (COVID‐19), there was a dearth of therapeutic options and nearly 1 in 3 patients died from the disease. By the summer of 2020, as deaths from the disease declined nationally, multiple single‐center studies began to report declining mortality of patients with COVID‐19. To evaluate the effect of COVID‐19 on hospital‐based mortality, we searched the Vizient Clinical Data Base for outcomes data from approximately 600 participating hospitals, including 130 academic medical centers, from January 2017 through December 2020. More than 32 million hospital admissions were included in the analysis. After an initial spike, mortality from COVID‐19 declined in all regions of the country to under 10% by June 2020 and remained constant for the remainder of the year. Despite this, inpatient, all‐cause mortality has increased since the beginning of the pandemic, even those without respiratory failure. Inpatient mortality has particularly increased in elderly patients and in those requiring intubation for respiratory failure. Since June 2020, COVID‐19 kills one in every 10 patients admitted to the hospital with this diagnosis. The addition of this new disease has raised overall hospital mortality especially those who require intubation for respiratory failure. Highlights: Inpatient mortality from COVID‐19 fell from 22% in March to under 10% in June and remained at similar levels for the remainder of 2020. There was an increase in all‐cause, inpatient mortality since the beginning of the pandemic, even in those without respiratory failure. Only patient with respiratory failure who required intubated had an increase in average inpatient mortality.